2017
DOI: 10.2134/jeq2016.07.0262
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Rice Agriculture to Methylmercury in Surface Waters: A Review of Data from the Sacramento Valley, California

Abstract: Methylmercury (MeHg) is a bioaccumulative pollutant produced in and exported from flooded soils, including those used for rice (Oriza sativa L.) production. Using unfiltered aqueous MeHg data from MeHg monitoring programs in the Sacramento River watershed from 1996 to 2007, we assessed the MeHg contribution from rice systems to the Sacramento River. Using a mixed‐effects regression analysis, we compared MeHg concentrations in agricultural drainage water from rice‐dominated regions (AgDrain) to MeHg concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…1). Butte and Yolo are located within the area studied by Tanner et al (2017) who reported similar irrigation and drainage water MeHg concentrations and seasonal patterns.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…1). Butte and Yolo are located within the area studied by Tanner et al (2017) who reported similar irrigation and drainage water MeHg concentrations and seasonal patterns.…”
Section: Resultsmentioning
confidence: 89%
“…Finally, decomposing rice straw may promote Hg(II)‐methylation by providing labile organic carbon, if the Hg(II)‐methylating microbes are limited by carbon (Marvin‐DiPasquale et al, 2014; Windham‐Myers et al, 2014b). However, the relationship between increased MeHg production and bioaccumulation or export is complex (Eagles‐Smith et al, 2014; Zhu et al, 2015; Tanner et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations